IMPROVING THE CHEMICAL PROPERTIES OF ACIDIC SOIL WITH AFFORDABLE LIME APPLICATION FOR INCREASING POTATO GROWTH AND YIELDS IN SEDIE DISTRICT, NORTHWESTERN ETHIOPIA - S. A. Yenesew (مجلة الأنبار للعلوم الزراعية)
Soil acidity remains a critical issue in Ethiopia, particularly in the highland regions, where over 43% of arable lands has low pH levels. Enhancing the chemical properties of the soil and subsequent potato growth and yield through affordable lime application is a critical area of agricultural research in the country. This study examined the effects of various lime application methods in enhancing the chemical properties of acidic soils on the growth, yields, and economic returns of potato cultivation. Each experimental plot had gross and net sizes of 2.1 m × 4.5 m (9.45 m²) and 1.5 m × 3 m (4.5 m²), respectively. The buffer method application involved a range of 2.5 t ha⁻¹ to 10 t ha⁻¹, while the exchangeable acidity method was from 0.84 t ha⁻¹ to 3.36 t ha⁻¹. The experiment layout included lime treatments of full broadcast, fractional, and drill-applied methods, evaluated against a control. Results showed that lime application significantly (P ≤ 0.01) enhanced soil chemical properties, achieving a pH of 6.26, exchangeable acidity 0.32 Cmol(+) kg⁻¹, exchangeable aluminum 0.00 Cmol(+) kg⁻¹, cation exchange capacity 29.43 Cmol(+) kg⁻¹, available phosphorus of 13.32 mg kg⁻¹, and organic carbon of 2.06%. Additionally, potato productivity reached 26.21 t ha⁻¹ for total yield with the full buffer method (FBM). In particular, 0.25 EAM demonstrated a superior marginal rate of return (MRR) of 829%, indicating an optimal balance between yield gains and economic feasibility. These findings reveal that partial lime applications offer an affordable alternative for smallholder farmers.